INTEGRASI TEORI TRAIT AND FACTOR DENGAN KONSELING KARIR BERBASIS ISLAM - Ade Rovita Nora; Widya Sagita; Masril Masril (STKIP Pesisir Selatan, 2026)
This study aims to examine the integration of Trait and Factor theory with Islamic values in career counseling in order to develop a more holistic and meaningful career decision-making model. The research employs a qualitative approach using a library research method, through the analysis of relevant scientific literature. Data were analyzed using content analysis techniques to identify, categorize, and synthesize key concepts related to individual characteristics, job requirements, and Islamic values in career selection.The findings indicate that Trait and Factor theory plays an important role in helping individuals understand their potential and align it with job demands in a rational manner. However, this approach has limitations, as it does not fully accommodate the dimensions of values and spirituality. Therefore, this study proposes an integrative conceptual model that incorporates Islamic values as a filtering mechanism in career decision-making, including intention (niyyah), permissibility (halal), social benefit, and orientation toward blessing (barakah). The implications of this study suggest that integrating psychological and spiritual aspects in career counseling can enhance self-understanding, clarity of career choices, career adaptability, and overall life satisfaction.